Factors Leading to Premature Birth and Modern Clinical Diagnostic Methods (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Preterm labor (regular uterine contractions that result in cervical dilatation) is considered preterm. Risk factors include rupture of membranes, uterine anomalies, infection, history of preterm labor, multiple pregnancies, and fetal or placental abnormalities. The diagnosis is made on the basis of clinical findings. Causes are identified and, if possible, eliminated. Treatment usually includes bed rest, tocolytic therapy (if labor is ongoing), corticosteroids (e.g., if gestational age < 34 weeks [see below]), and possibly magnesium sulfate (if gestational age < 32 weeks). Antistreptococcal antibiotics are prescribed until vaginal and anal cultures are negative for group B streptococci.